1977
DOI: 10.3133/ofr77776
|View full text |Cite
|
Sign up to set email alerts
|

The Pierre Shale, northern Great Plains; a potential isolation medium for radioactive waste

Abstract: The purpose of this reconnaissance is to assess the potential of the Pierre Shale, of Late Cretaceous age, as a possible isolation medium for radioactive wastes. The regional stratigraphic and structural setting of the Pierre Shale in the northern Great Plains is summarized from subsurface data.Geologic attributes mapped and employed in the identification of areas warranting further evaluation are: depth to the base of the Pierre Shale, shale thickness, overburden thickness, lithology and mineralogy of the sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Gonzales and Johnson (1984) used "shale" as the general term for desirable rock types; however, the more clay-rich, plastic, less indurated, and less fissile shales could be preferred for repository purposes. Similar to Shurr's (1977) recommendation, Gonzales and Johnson concluded that the most desirable host rock units should be between 300 and 900 m below ground level, at least 75 m thick, relatively homogeneous in composition, and in an area of low seismicity and favorable hydrology that is not likely to be intensively exploited for subsurface resources. Figure 1-1 is a map of the U.S. showing distribution of principal shale formations by general geologic age and region, for which broad geologic and hydrologic data are reviewed by Gonzales and Johnson (1984).…”
Section: Shales and Argillaceous Strata In The United Statesmentioning
confidence: 95%
See 1 more Smart Citation
“…Gonzales and Johnson (1984) used "shale" as the general term for desirable rock types; however, the more clay-rich, plastic, less indurated, and less fissile shales could be preferred for repository purposes. Similar to Shurr's (1977) recommendation, Gonzales and Johnson concluded that the most desirable host rock units should be between 300 and 900 m below ground level, at least 75 m thick, relatively homogeneous in composition, and in an area of low seismicity and favorable hydrology that is not likely to be intensively exploited for subsurface resources. Figure 1-1 is a map of the U.S. showing distribution of principal shale formations by general geologic age and region, for which broad geologic and hydrologic data are reviewed by Gonzales and Johnson (1984).…”
Section: Shales and Argillaceous Strata In The United Statesmentioning
confidence: 95%
“…The depositional settings changed over geologic time and location, and included areas that have more or less clay, silt, or sand as percentages. Although the current study is not a siting exercise, because of the wide availability of potential host formations in the U.S., a repository site could readily be located with attributes such as those identified by Shurr (1977):…”
Section: Shales and Argillaceous Strata In The United Statesmentioning
confidence: 99%
“…On-land basalts however should be considered as an alternative host rock. In Shales and Argillaceous media potential host formations, a repository site could readily be located with attributes such as those identified by Shurr [1977]:…”
Section: Methodology Acceptable Generic Sitesmentioning
confidence: 99%
“…We arranged the proposed sites according to these numbers. The procedure for using ODM can be summarized as follows: model the problem as a hierarchy containing the decision goal, the options for reaching it, and the criteria for evaluating the options; establish priorities among the elements of the hierarchy; synthesize these judgments to yield a set of overall priorities for the hierarchy; check the consistency of the judgments; come to a final decision based on the results of this process [25]. The four potential sites are located in the western desert of Egypt figure [4]; in the south west part.…”
Section: Methodology Acceptable Generic Sitesmentioning
confidence: 99%
“…Figure 8 shows the areal distribution of shale in the USA along with depth to top mapping of formation units. In collecting data from several potential units, we also considered the recommendations of Hansen et al (2010) and Shurr (1977):…”
Section: Properties Of the Argillaceous Host Formationmentioning
confidence: 99%